PENGEMBANGAN MEDIA MANIPULATIF TUSUK GIGI DAN PLASTISIN UNTUK MEMBANDINGKAN CIRI BANGUN DATAR DI KELAS V INKLUSIF - Nurlita Andayani; Unik Ambar Wati; Evy Nur Rochmah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research to develop a manipulative media based on toothpicks and plasticine in the material, compare the characteristics of flat buildings in class V inclusive, and determine the level of feasibility of the developed media. This research uses the method (R&D) with the ADDIE development model which includes the analysis, design, development, and implementation stages. The subject is inclusive class V students at Jogja Green School. Data collection techniques use observation, interviews, documentation, and questionnaires. The research instruments were questionnaires for validation of material experts, media experts, teacher responses, and student responses. The results of the research on manipulative media based on toothpicks and plasticine were successfully developed for learning the material comparing the characteristics of flat buildings in inclusive class V. The media is designed using toothpicks as a representation of the sides of a flat building and plasticine as a connecting point of the corner so that students can arrange various forms of flat buildings directly and concretely. The results of the validation describe the development of the media as very feasible. The validation of the material experts obtained a percentage of 92%, while the media experts obtained a percentage of 94%. Then, the results of the educator's response were 95% and the student's response was 96% categorized as very good. So the results prove that toothpick and plasticine media are suitable for use in elementary school mathematics teaching, especially inclusive classes. The use of manipulative media is able to make it easier to conceptualize real flat buildings from exploratory activities and learning experiences. The media also increases the active involvement, enthusiasm, and enthusiasm of its students to learn. Thus, manipulative media based on toothpicks and plasticine has the potential to support more adaptive, meaningful, and fun mathematics learning in inclusive classes in elementary schools. ABSTRAK Penelitian ini bertujuan untuk mengembangkan media manipulatif berbasis tusuk gigi dan plastisin pada materi membandingkan ciri-ciri bangun datar di kelas V inklusif serta mengetahui tingkat kelayakan media yang dikembangkan. Penelitian ini menggunakan metode (R&D) dengan model pengembangan ADDIE yang meliputi tahap analysis, design, development, dan implementation. Subjeknya peserta didik kelas V inklusif di Jogja Green School. Teknik pengumpulan data menggunakan observasi, wawancara, dokumentasi, dan angket. Instrumen penelitian yaitu angket validasi ahli materi, ahli media, respons guru, dan respons peserta didik. Hasil penelitian media manipulatif berbasis tusuk gigi dan plastisin berhasil dikembangkan untuk pembelajaran materi membandingkan ciri-ciri bangun datar di kelas V inklusif. Medianya dirancang menggunakan tusuk gigi sebagai representasi sisi bangun datar dan plastisin sebagai penghubung titik sudut sehingga peserta didik dapat menyusun berbagai bentuk bangun datar secara langsung dan konkret. Hasil validasinya mendeskripsikan pengembangan medianya berkategori sangat layak. Validasi ahli materinya memperoleh persentase 92%, sedangkan ahli medianya memperoleh persentase 94%. Kemudian, hasil respons pendidiknya 95% dan respons siswanya 96% berkategori sangat baik. Maka hasilnya tersebut membuktikan media tusuk gigi dan plastisin layak dipakai pada pengajaran matematika sekolah dasar, terkhusus kelas inklusif. Penggunaan media manipulatif mampu memudahkan mengkonsepkan secara nyata bangun datar dari aktivitas eksploratif serta pengalamannya belajar. Media juga meningkatkan keterlibatan aktif, antusiasme, serta semangat siswanya belajar. Dengan demikian, media manipulatif berbasis tusuk gigi dan plastisin berpotensi menunjang pembelajaran matematika yang lebih adaptif, bermakna, dan menyenangkan pada kelas inklusif di sekolah dasar.